Olivine and dissolved alkalinity trigger different bacterial community shifts in water and oyster gills: insights from a mesocosm experiment - Antoni, Dominik; Rump, Marco; Gerdts, Gunnar (Frontiers in Microbiomes, 2025)
Ocean Alkalinity Enhancement (OAE) is a proposed marine carbon dioxide removal strategy that increases seawater buffering capacity and CO2 uptake through the addition of alkaline substances. While OAE shows promise as a climate mitigation tool, its ecological implications remain poorly understood, particularly regarding microbial communities. This paper provides a risk assessment of two different OAE strategies: alkalization with olivine and alkalization with addition of dissolved sodium hydroxide (NaOH). With a mesocosm experiment designed to simulate coastal OAE application, European flat oysters (Ostrea edulis) were chronically exposed to alkalinity-enhanced seawater at two concentrations (250 and 500 µmol·L-¹) derived either from olivine weathering or addition with NaOH. The bacterial community composition of both alkalization types was assessed with amplicon sequencing of the 16S rRNA gene and ecotoxicological impacts were compared to a non-alkalized control. The sampling strategy included samples of the treated waters and the gill microbiome of Ostrea edulis. Our results show that the alkalization type was the primary driver of microbial shifts in the bacterial community of the water samples. Olivine treatments caused distinct taxonomic changes, including an increase in Gammaproteobacteria and Flavobacteriales and a marked decline in Alphaproteobacteria and SAR11 clade. Olivine-treated waters showed reduced richness and evenness. In contrast, dissolved alkalinity treatments produced minimal changes compared to untreated controls. The analysis of the oyster gill microbiome detected a response that was stronger influenced by alkalinity concentration than by alkalization type. Notably, high-alkalinity olivine treatments favored potentially pathogenic Vibrios. Together, these findings highlight that OAE method selection significantly influences bacterial community composition in both marine and host-associated microbiomes. In our experiment, olivine-based OAE posed a greater environmental risk than dissolved OAE. Our study provides insights on the impact of different OAE scenarios, representing a first step toward future field trials and applications.